Determinantes de inadimplência e de recuperação de crédito em um banco de desenvolvimento - Gustavo Henrique de Oliveira Amaral (2015)
Credit risk management has been receiving greater attention from economic actors and academics due to recent financial crisis triggered in the banking sector. Development banks are financial institutions with specific purposes of performance in government policies for the development of the local economy and to generate social welfare. As financial institutions, development banks must ensure its financial sustainability. In most recent years it has been recognized the influence of internal factors, such as the characteristics of the company and its partners, contractual conditions and the historical rapport with the credit lender, as well as external factors, such as the macroeconomic environment, as determinants for noncompliance or for credit recovery of credit borrowers companies. In this context, the main purpose of this research was to identify the conditioning factors of non-performing loans and credit recovery in the credit portfolio of a development bank based on information available regarding 20.241 loans provided to micro and small enterprises between November 2009 and November 2014. To achieve the goals of this study, it was estimated four models of non-performing loans and one model of credit recovery by logistic regression. The results indicated contributions of individual, contractual, rapport and macroeconomic factors either for determination of non-performing loans or for credit recovery. The recognition of the influence of these various factors can contribute to a better credit management regarding lending procedures and collection of default credits, creating greater organizational efficiency.